Determinants and Strategies for Strengthening Junior High Students’ Numeracy in the Indonesia–Timor Leste Border Region - Yovita Maria Palla; Aloisius Loka Son; Hendrika Bete; Javier García-García; Camilo Andrés Rodríguez-Nieto (CV. Samuel Manurung and Co, 2026)
The low numeracy skills of students in Indonesia remains a major challenge in many schools, including Junior high school students in the border area of ​​the Republic of Indonesia and the Democratic Republic of Timor Leste. The purpose of this study is to describe the level of students’ numeracy skills, identify aspects that still need improvement, explore the factors affecting students’ numeracy skills, and examine the efforts made to support numeracy development among junior high school students. This study employs a qualitative research design with a case study approach, conducted at one Junior High School in Kefamenanu City, Indonesia, during the odd semester of the 2024/2025 academic year. The participants were 21 eighth-grade students who completed a written test, followed by interviews with six students, their parents, and the mathematics teacher. Test items and interview guidelines were used to collect data. Results indicate that students’ numeracy skills are still relatively low, as reflected in the low average test scores. The numeracy aspects that require the most improvement are application and reasoning. Factors influencing numeracy skills include internal factors-such as interest, motivation, understanding, and attitude-and external factors, including the learning environment, facilities and infrastructure, parental involvement, and teaching strategies. Efforts to enhance numeracy skills include increasing students’ interest and motivation, strengthening conceptual understanding, developing application and reasoning skills, and implementing context-based learning strategies